Perception of Women regarding Respectful Maternity Care during Facility-Based Childbirth - Pratima Pathak; Bijaya Ghimire (Obstetrics and Gynecology International)
Background. Respectful care during childbirth has been described as “a universal human right that encompasses the principles of ethics and respect for women’s feelings, dignity, choices, and preferences.” Many women experience a lack of respectful and abusive care during childbirth across the globe. Objective. This study aimed to determine women’s perception of respectful maternity care (RMC) during facility-based childbirth. Method. A descriptive cross-sectional study was conducted among 150 mothers admitted to the maternity ward of Nepal Medical College and Teaching Hospital using a purposive sampling technique. Data were collected through an interview technique by using a validated tool containing 15 items each measured on a scale of 5. Statistical Package for Social Science (SPSS) version 16 was used for data analysis. Frequency, percentage, mean score, standard deviation, chi-square test, and binary logistic regression were used to analyze descriptive and inferential statistics. Results. In total, 84.7% of the women reported that they have experienced overall RMC services with a mean score ± SD (61.70 ± 12.12). Though the majority of the women reported that they have experienced RMC services, they also revealed that they have experienced disrespectful care in various forms such as being shouted upon (30.0%), being slapped (18.7%), delayed service provision (22.7%), and not talking positively about pain and relief during childbirth (28.0%). Likewise, length of stay, parity, and time of delivery were found as factors that influenced friendly care (COR = 0.383, 95% CI: 0.157–0.934), abuse-free care (COR = 3.663, 95% CI: 1.607–8.349), and timely care (COR = 2.050, 95% CI: 1.031–4.076) dimensions of RMC, respectively. Conclusion. Even though RMC emphasizes eliminating disrespectful and abusive environment from health facilities, 15.0% of participants perceived that they have not experienced overall RMC services. So, the health facility should focus on the interventions which ensure that every woman receives this basic human dignity during one of the most vulnerable times in their lives.